Systemic Mastocytosis Associated with Splenic Marginal Zone Lymphoma with Villous Lymphocytes - Fernández-Torres, R. (Hindawi Publishing Corporation, 2011)
The development of a second haematological disease during the course of systemic mastocytosis is a well-known phenomenon. In most of the cases, they consist of myelodysplasia or myeloproliferative disorders. The association with lymphoproliferative disorders has also been described, but it is uncommon and the relationship is not well established. We report a patient diagnosed with systemic mastocytosis who three years later developed a splenic marginal zone lymphoma with villous lymphocytes.